2015
DOI: 10.1159/000365497
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety: What Is It All about?

Abstract: Patient safety is a major concern in health care systems worldwide. Patients with serious conditions, multimorbidity, and with intense and fragmented health care utilization, like end-stage renal disease (ESRD) patients, are at increased risk for suffering adverse events. In this chapter, the fundamental terms and concepts of patient safety are introduced. Essential epidemiological data relating to the frequency of adverse events and medical errors are provided. The chapter reports important safety threats for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
4
0
3
Order By: Relevance
“…The incidence rates of AEs in critical care can range from 5-15% of all Intensive Care Unit hospitalizations. 14 The high prevalence of AEs in HD has also been found in a Brazilian study that identified 80.3% of AEs per patient, 15 corroborating with the findings of this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The incidence rates of AEs in critical care can range from 5-15% of all Intensive Care Unit hospitalizations. 14 The high prevalence of AEs in HD has also been found in a Brazilian study that identified 80.3% of AEs per patient, 15 corroborating with the findings of this study.…”
Section: Discussionsupporting
confidence: 90%
“…17 The type of AE with the highest prevalence found in this study is similar to the data found in literature, which also indicates medication error in patients on hemodialysis treatment as the most common type of AE . 4,14,[18][19] The National Agency of Sanitary Surveillance defines medication error as any preventable event that may lead to the inappropriate use of a medication under the control of the health team or even the patient himself, that leads to, or has the potential to lead to, harm to the patient. 20 In view of this concept, during data collection it was noticed that most medication errors occurred due to noncompli-ance with the prescription, mainly the omission of administrating erythropoietin and iron hydroxide saccharate, which may be justified by the fact that the patients of the service are responsible for bringing the medications that will be administered by the nursing staff during the HD sessions, according to their monthly prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Medical errors can be classified in different categories besides errors of execution and omission. There can be errors at the sharp end , meaning in activities close to the patient, and errors on the blunt end , where the problem relates more to organizational issues and/or a poor process design (2). Slips and lapses are failures of a schematic behaviour and are often related to stress and fatigue.…”
Section: The Concept Of Patient Safetymentioning
confidence: 99%
“…Patients with end-stage renal disease (ESRD) suffer from multiple comorbidities and are exposed to medical treatments for life with an extended risk to for a potentially preventable adverse event. Table I summarizes patient safety topics that are closely related to persons with ESRD undergoing haemodialysis (2, 9, 10).…”
Section: Safety In Dialysis Access Patientsmentioning
confidence: 99%
“…Even if an AVF is created with an appropriate vein and it successfully matures, puncturing to obtain vascular access is often difficult because of the deep positioning of the matured vessel. In such cases, inappropriate needling can lead to infiltration and aneurysm and hematoma formation, ultimately damaging the hemodialysis route [5]. To resolve this problem, superficialization of the vessel is crucial [6,7].…”
Section: Introductionmentioning
confidence: 99%